Treatment of malocclusion with orthodontic aligners in a patient with mixed dentures - Giacomini, Carla; Hilgenberg, Sérgio Paulo (Seven Editora, 2023)
Malocclusion is one of the major oral problems faced by the world's population. With the advancement of technology and dentistry, over the years, many treatments have been taking space in the labor market, and one of the newest is the invisible appliances. Guaranteeing, mainly, the aesthetics, they provide immeasurable comfort to the patients, compared to traditional orthodontics. This study was carried out on a 10-year-old female patient, over approximately 5 months, with satisfactory results at the end of treatment, which proves that orthodontic aligners have a high success rate in patients with mixed dentition, depending greatly on their collaboration. DOI:https://doi.org/10.56238/devopinterscie-245